2004
DOI: 10.1111/j.1751-0813.2004.tb12683.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey for papillomatous digital dermatitis in Australian dairy cattle

Abstract: Anecdotal reports and analysis of biopsy material confirm that a condition similar to PDD does occur sporadically in dairy cattle in southern Australia. However, this condition has so far not been shown to be associated with the presence of spirochaetes in the lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Probably, this is the reason why lameness was not the first clinical sign noticed by the farmer at the present study. In support to this finding, other researchers [12,13] referred that lameness is not a significant finding among the affected cows.…”
Section: Resultssupporting
confidence: 51%
“…Probably, this is the reason why lameness was not the first clinical sign noticed by the farmer at the present study. In support to this finding, other researchers [12,13] referred that lameness is not a significant finding among the affected cows.…”
Section: Resultssupporting
confidence: 51%
“…The negative results for treponemes in our samples may be due to the low sensitivity of the PCR rather than the absence of treponemes in the samples. The same conclusion was drawn from five biopsies of erosive dermatitis‐lesions, which were obtained from a veterinary practice in Tasmania, Australia. In that study, there were no Spirochaete organisms observed by silver staining, and these researchers suggest that their finding indicated that other hoof disorders with common conditions are easily mistaken for DD.…”
Section: Discussionmentioning
confidence: 64%
“…Treponema ‐species are difficult to culture, so a more successful way to identify these species is by PCR. Another commonly used technique for analysis is haematoxylin‐eosin (HE) staining or silver staining. However, there is no gold standard test to confirm a macroscopic diagnosis of DD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have linked multiple bacterial species to DD lesions 5. Nonetheless, spirochetes, of the genus Treponema , have been consistently found deep within the dermis of infected cows 6–8. DD largely appears to be multifactorial including a combination of intrinsic and environmental risk factors: stock purchase, low parity, early lactation and moist unhygienic housing conditions 2 9 10…”
Section: Introductionmentioning
confidence: 99%